A Comparative Theoretical Analysis of Language Acquisition Models in Children Under Five - Pradana, Sandi (LinguaScopes: International Journal of Language Education, 2025)
This comparative theoretical analysis investigates major language acquisition models to understand how children under five acquire language. Early language development is crucial for cognitive and social growth, yet existing literature lacks a focused comparative analysis of these models for this specific age group. This study aims to describe dominant theoretical models, analyze their core assumptions, mechanisms, and relevance to early childhood language development, and evaluate their strengths and limitations. Employing qualitative library research and comparative analysis, data was collected from seminal works by Skinner (behaviorist), Chomsky (nativist), Piaget (cognitive), Vygotsky (social interactionist), and Tomasello (usage-based), alongside peer-reviewed journals and scholarly books from 1960 to 2025. Findings indicate that no single model fully explains all facets of language acquisition in young children. Behaviorism highlights environmental reinforcement, nativism emphasizes innate linguistic structures, cognitive theory links language to general intellectual development, social interactionism stresses the role of social context and scaffolding, and usage-based models focus on pattern-finding and communicative intentions. The comparative approach reveals complementary strengths, suggesting that integrated, multidimensional frameworks are most effective for understanding and supporting early language development.